Solvent induced 4, 4, 4-trifluoro-1-(2-naphthyl)-1, 3-butanedione Cu(II) complexes: Synthesis, structure, DFT calculation and biocidal activity. (1st August 2019) - Hema, M.K.; Karthik, C.S.; Pampa, K.J.; Manukumar, H.M.; Mallu, P.; Warad, Ismail; Lokanath, N.K.
Graphical abstract: Two novel pseudopolymorphic copper complex crystals, [Cu(C14 H8 O2 F3 )2 (C2 H6 OS)2 ] (1 ) and [Cu(C14 H8 O2 F3 )2 (C3 H7 NO)] (2 ) were grown and characterized by UV–Vis, FTIR, EDS and single crystal XRD. With the aid of induced solvents, both complexes form different coordination sphere and exhibit the uniqueness in constructing the supramolecular architecture. Interestingly, owing to the intermolecular short interaction between fluorine atoms with adjacent molecules, complex2 construct the three different supramolecular synthons through rhomboid channels. Isomorphic differences between the complexes predominantly evince on the formation of different graph-set descriptors which promote the distinct molecular packing. For the purpose of investigating structural topographies, DFT calculations were done for both complexes and were fully optimised using B3LYP level. The predicted geometry parameters are compared with their corresponding X-ray crystallographic data. Complexes are biocompatible in nature and potent biocidal (MIC 50 µg/mL) properties against perilous methecilline-resistant Staphylococcus aureus (MRSA) through membrane destabilization. Complex2 could be a potential candidate to combat drug-resistant infectious agents in future, can be warranted. Abstract: Two novel pseudopolymorphic copper complex crystals, [Cu(C14 H8 O2 F3 )2 (C2 H6 OS)2 ] (1 ) and [Cu(C14 H8 O2 F3 )2 (C3 H7 NO)] (2 ) were grown and characterized by UV–Vis, FTIR, EDS and single crystal XRD. With the aid of induced solvents, both complexes form different coordination sphere and exhibit the uniqueness in constructing the supramolecular architecture. Interestingly, owing to the intermolecular short interaction between fluorine atoms with adjacent molecules, complex2 construct the three different supramolecular synthons through rhomboid channels. Isomorphic differences between the complexes predominantly evince on the formation of different graph-set descriptors which promote the distinct molecular packing. For the purpose of investigating structural topographies, DFT calculations were done for both complexes and were fully optimised using B3LYP level. The predicted geometry parameters are compared with their corresponding X-ray crystallographic data. Complexes are biocompatible in nature and potent biocidal (MIC 50 µg/mL) properties against perilous methicillin-resistant Staphylococcus aureus (MRSA) through membrane destabilization. Complex2 could be a potential candidate to combat drug-resistant infectious agents in future, can be warranted.